How Technology, Gender annd Education Affected Financial Inclusions - Astha Amalia Dyah Sayekti; Taofik Hidajat (Journal of Economics and Business, 2021)
This paper highlights the role of technology, gender and education factors in financial inclusion. A sample of 995 people was taken from the Global Findex Database, World Bank. Using logistic regression, this research concluded that technology and education had a positive effect on financial inclusion. The higher the use of technology and education level, the more likely the respondent has an account at a financial institution. However, gender does not affect financial inclusion. Men and women have the same probability in financial inclusion.